EFEKTIVITAS CHATGPT DALAM STRATEGI PEMASARAN KONTEN PADA USAHA MIKRO KECIL MENENGAH (UMKM) KOTA MEDAN - Hidayah Yoanna Putri; Laelis Neni; Nur Lela (Smart Education, 2025)
Abstract:The development of artificial intelligence since 2020 has had a significant impact on business practices, including digital marketing. One innovation in AI, ChatGPT, enables the rapid, creative, and audience-tailored automated creation of marketing content. The purpose of this study is to assess the effectiveness of ChatGPT in supporting content marketing strategies for micro, small, and medium enterprises in Medan. This study employed a mixed-method approach, using a quantitative approach through a Likert scale questionnaire to evaluate perceptions of effectiveness, as well as a qualitative approach involving in-depth interviews and content analysis of promotions before and after the use of ChatGPT. The research subjects consisted of MSMEs engaged in the culinary, fashion, and handicraft sectors in the city of Medan. Data analysis was conducted using descriptive statistics and effectiveness testing for quantitative data, as well as thematic analysis for qualitative data. It is hoped that the results of this study will show that the application of ChatGPT can improve content quality, audience interaction, and efficiency in marketing strategies, despite challenges such as a lack of digital literacy and limited resources. This study is expected to contribute theoretically to AI-based digital marketing literature and serve as a practical guide for MSMEs to optimise their content marketing strategies by utilising ChatGPT. Â Keywords: ChatGPT; content marketing; SMEs; artificial intelligence; digital strategy.Â Abstrak: Perkembangan kecerdasan buatan (AI) sejak 2020 telah membawa perubahan besar dalam praktik bisnis, termasuk strategi pemasaran digital. Salah satu inovasi AI, ChatGPT, memungkinkan pembuatan konten pemasaran secara otomatis dengan cepat, kreatif, dan sesuai kebutuhan audiens. Penelitian ini bertujuan untuk mengevaluasi efektivitas ChatGPT dalam mendukung strategi pemasaran konten pada Usaha Mikro, Kecil, dan Menengah (UMKM) di Kota Medan. Penelitian menggunakan metode campuran (mixed methods), dengan pendekatan kuantitatif melalui kuesioner skala Likert untuk menilai persepsi efektivitas, serta pendekatan kualitatif melalui wawancara mendalam dan analisis konten promosi sebelum dan sesudah penggunaan ChatGPT. Subjek penelitian terdiri dari UMKM di sektor kuliner, fashion, dan kerajinan di Kota Medan. Data dianalisis menggunakan statistik deskriptif dan uji efektivitas untuk data kuantitatif, serta analisis tematik untuk data kualitatif. Hasil diharapkan menunjukkan bahwa pemanfaatan ChatGPT dapat meningkatkan kualitas konten, interaksi audiens, dan efisiensi strategi pemasaran, meskipun terdapat kendala seperti literasi digital dan keterbatasan sumber daya. Penelitian ini memberikan kontribusi teoretis pada literatur pemasaran digital berbasis AI dan panduan praktis bagi UMKM dalam mengoptimalkan strategi pemasaran konten menggunakan ChatGPT.Â Kata kunci: ChatGPT; pemasaran konten; UMKM; kecerdasan buatan; strategi digital.